Concurrence of Grave's disease and Hashimoto's thyroiditis. Issue 12 (December 1977) - Sato, T; Takata, I; Taketani, T; Saida, K; Nakajima, H
Abstract : Early histological changes in the thyroid gland were examined in 30 patients with juvenile thyrotoxicosis, by means of needle biopsy. Based on the degree of lymphocytic infiltration and degenerative changes in follicular epithelium, results were classified into four groups. A: hyperplastic changes without cellular infiltration (6 patients, 20%); B: hyperplastic changes with areas of focal thyroiditis less than 30% of specimen (10 patients, 33%); C: those with 30 to 60% areas ot thyroiditis (10 patients, 33%); D: almost diffuse thyroiditis (4 patients, 13%). Moderate to severe lymphocytic thyroiditis was frequently present in the early stage of hyperplastic thyroid glands. The clinical significance of the 4 histological groups was evaluated. Neither clinical signs nor routine laboratory tests could differentiate these groups except group D, in which thyrotoxic signs were mild and transient. However, serum antithyroid antibodies tended to increase in accordance with severity of thyroiditis. The rate of remission was high in groups C and D, whereas relapse was frequent in group A. These results suggest that Grave's disease and chronic lymphocytic thyroiditis are closely related in the early stage of thyrotoxicosis in children, and that the clinical course may be considerably altered by the degree of associated thyroiditis.